miPEP31 alleviates sepsis development by regulating Chi3l1-dependent macrophage polarization - Yu Zhou; Yuan Yuan; Xuanqi Yao; Lin Wang; Liangfang Yao; Daolin Tang; Feng Chen; Jinbao Li (Biology Direct)
Abstract Background Sepsis is a severe condition characterized by multiple organ dysfunction resulting from an imbalanced host immune response to infections. miRNAs play a crucial role in regulating various biological processes. However, the precise role of miR-31 in the immunopathology of sepsis remains poorly understood. Methods The concentration of hsa-miR-31-5p in patients with sepsis (both survivors and non-survivors) and healthy individuals was assayed. Using an experimental sepsis model of caecal ligation and puncture (CLP), the impact of mmu-miR-31-5p on survival, organ injury, and inflammation was evaluated. Additionally, the effect of mmu-miR-31-5p on macrophage polarization through Chi3l1 was investigated. Lastly, the therapeutic effects of miPEP31 on experimental sepsis were examined. Results The results of miRNA sequencing (miRNA-seq) and quantitative polymerase chain reaction (q-PCR) analyses identified hsa-miR-31-5p as a potential biomarker for patients with sepsis, with non-survivors showing higher levels of hsa-miR-31-5p in peripheral blood mononuclear cells (PBMCs) compared to survivors. Functional studies conducted on peritoneal elucidated macrophages (PEMs) demonstrated that mmu-miR-31-5p inhibits M2 polarization in macrophages by downregulating Chi3l1. The utilization of miPEP31 as a therapeutic intervention had a substantial impact on reducing mortality rates, mitigating organ damage, inducing macrophage polarization towards the M2 phenotype, and suppressing the inflammatory response in murine models of severe sepsis. Conclusions The suppression of miR-31 in sepsis plays a protective role in the host defense response by upregulating Chi3l1, highlighting the potential therapeutic efficacy of miPEP31 in sepsis treatment. Graphical abstract